Abnormal Levels of Pepsinogen I and Gastrin 17 in a case of Ménétrier Disease: Pepsinogen I and G17 in Ménétrier Disease. - Crafa, Pellegrino; Franceschi, Marilisa; Franzoni, Lorella; Di Mario, Francesco (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: We describe a case of Ménétrier disease, occurred in female patient. Methods: We decide to assess by non-invasive way (serum pepsinogens and gastrin 17) the secretory status of gastric mucosa, to confirm previous data of the literature, claiming high levels of both acid secretion and hypergastrinemia in this rare pathological condition. Results and Conclusion: We find in the subject the highest values of pepsinogen 1 – a marker of acid secretion – never described in the literature to our knowledge: 1940 mcg/L, being normal values ranging from 30-160 mcg/L. Similarly, gastrin 17, produced 90% in the antrum and responsible for negative acid feedback, was very high: 139 pg/L, ranging normal values between 1-10 pg/L. (www.actabiomedica.it)